Peran Teknologi Terhadap Transformasi Sosial Dari Ojek Konvensional Ke Ojek Online - Ani Linta Sari; Ardhia Pramesty Regita Cahyani; Yolanda Naomi Martdina (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The development of technology has progressed rapidly in Indonesia, especially with the shift from conventional ojek to online ojek. Online ojek now comes to facilitate the public in accessing transportation simply through an application. This study employs a descriptive qualitative research approach with a phenomenological perspective. Data collection techniques were carried out through direct observation, in-depth interviews, and documentation. The results of this study indicate that the current technological advancements do not guarantee that conventional ojek drivers will switch to online ojek. Their reluctance to become online ojek drivers is due to lower income earned as online ojek drivers and age factors that make it difficult for them to understand technology, particularly in using applications. The researcher uses the theory of modernization from Talcott Parsons' pattern variables concept to analyze the change from conventional ojek to online ojek.